Post-COVID syndrome: an emerging global health issue in the aftermath of the SARS-COV-2 pandemic - Bhutta, Faisal Saeed; Rafiq, Kanwal (International Journal of Research in Medical Sciences, 2023)
SARS-CoV-19 started as acute respiratory tract infection in late 2019 and spread globally. It led to 65 million people affected worldwide and deaths of multimillion across the world. The term “post-COVID conditions” is an umbrella term for the wide range of physical and mental health consequences experienced by some patients that are present four or more weeks after SARS-CoV-2 infection, including by patients who had initial mild or asymptomatic acute infection.